Proportion of Bacillary and Morphological Indices of Untreated and Treated Suspected Leprosy Slit Skin Smear - Indriani Silvia; Parwati, Ida; Andriyoko, Basti; Rachmawati, Banundari; Sukartini, Ninik (Indonesian Journal of Applied Research (IJAR), 2025)
Indonesia is the third highest number of leprosy in the world with pockets of high endemicity spread across the archipelago. Leprosy diagnosis in control program include finding of acid fast bacilli (AFB) from slit skin smear (SSS) that assessed for the bacillary index (BI). The solid AFB form assessed for morphological index (MI). This study aimed to analyze the proportion of BI and MI of untreated and treated suspected leprosy SSS. This was a retrospective observational study on BI and MI from 117 suspected leprosy SSS secondary data. Of this, being males was the most prevalent in the age group 19-40 years with 91 untreated (84.6% acid fast bacilli, AFB) and 26 treated (80.8% AFB). Treated 2+ BI still high 23.8% from untreated BI 2+ 23.4%. Untreated MI >50 was found in 25.4% and treated MI >50 is still found in 19.1%. Bacillary index and MI support the diagnosis and detect the transmission of leprosy infection.